Dynamic model of optimum control of a credit portfolio of commercial bank with additional criterion of liquidity of temporary structure of assets and liabilities - M. A. Gadzhiagayev; M. A. Halikov (Путеводитель предпринимателя, 2020)
There is the statement, the formalized mathematical model of the numerical method for solving the dynamic two-level problem of formation and the management of the credit portfolio of commercial bank as part of the cumulative bank portfolio at consecutive time intervals. To the structure of criteria of optimum control of a portfolio along with the profitability and risk is also proposed to include the liquidity of temporary structure of assets and liability which allows to improve the financial stability of the bank in terms of possible «gaps» of liquidity associated with the excess of liabilities over assets in certain time intervals. Model of the first level includes monitoring, assess the quality of the loan portfolio and calculation of available funds of the bank for subsequent placement in loans. The second level model is the choice of parameters of credit and loan applications for the next time interval.